Lutero Interprete Dei Salmi Biblici (1513-1515) - Osculati, Roberto 1939- (2018)
The first exegetical lessons given in Wittenberg by the Augustinian monk Martin Luther about the biblical Psalms (1513-1515) have recently found a new edition (1993-2000). The lessons show an evident relationship with a long theological tradition going as far as Augustine, Cassiodorus, Gregory the Great, Bernard, Tauler, Nicholas of Lyra. Every human creature is deep involved in the consequences of the original sin. Only the grace of the Father, the redemption of Christ, the interior work of the Spirit shall grant justice and salvation. Should these spiritual gifts be missing, nature and law would only have a deadly meaning. However, the interest of the Luther's time church often goes to the Aristotelian philosophy of the nature, to the human traditions, to the administration of the present world. Until the last judgement the false Christianity of the human powers fights against the Christianity of the imitation of Christ under the cross.
Keywords: Agostino; Augustine; Luther; Luther, Martin, 1483-1546; Lutro; Bible. Psalms; Catholic Church; Grace; Psalms; Salmi; grazia